Persepsi Masyarakat Terhadap Pelestarian Nilai-Nilai Moral Bagi Perempuan di Desa Saukang Sinjai Timur - Resky Amalia; Abdul Rahman (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2023)
This research aims to determine society's perception of preserving moral values for women, to determine patterns of instilling moral values in women, and to determine the role of women in preserving moral values. To achieve this goal, qualitative research methods were used by means of observation, interviews and documentation. The data that has been obtained is then analyzed and interpreted based on theory and relevant research results. The results of the research show that preserving moral values for women is very important, where this preservation starts from the upbringing or teachings of each parent to their child and how a woman wants to apply these attitudes in the community by socializing with the local community. And the role of women in preserving moral values is by understanding morals themselves, then applying them wherever they are, whether in the family, school or community environment, and getting used to them so that these moral values do not fade.